Pembuatan Alat Peredam Suara Skala Praktikum - Abdul Kadir; Yuspian Gunawan; Muhammat Reskiyanto; Muh.Akbar; Ul Asri; Ramadhan (Piston: Jurnal Teknologi, 2024)
Noise is the occurrence of unwanted sounds including irregular sounds and sounds emitted by transportation and industry, so that in the long term it can disturb and endanger work concentration. The purpose of making this silencer test equipment is to determine the level of sound that can be heard properly. .Methodology used: In an impedance tube, two microphones are placed at one end of the impedance tube and a sound source is placed on the other side. Two microphones were placed between them which were used to measure differences in the acoustic impedance of the sound field produced. The results of the research carried out were the creation of a sound dampening device. This research was carried out in three stages, namely the stage of making sound dampening equipment. In this study, two types of specimens were used, namely from wood powder waste and cigarette butt waste with a thickness of 1 cm with a frequency used of 500 Hz, (wood dust = 0.0164. Cigarette butts = 0.0164) 1000 Hz (wood dust = 0 .0097, cigarette butts = 0.0114) and 1500 Hz.(wood dust = 0.0107, cigarette butts = 0.0139